Seroprevalence of foot and mouth disease virus infection in pigs from Zuru, Nigeria - L. U. Fakai; O. O. Faleke; A. A. Magaji; E. B. Ibitoye; B. R. Alkali (Veterinary World, 2015)
Aim: This study was conducted to determine the seroprevalence and distribution of foot and mouth disease virus (FMDV) infection in pigs from Zuru, Kebbi State, Nigeria. Materials and Methods: Cross-sectional serological surveys were conducted between May and December 2013 using the immunochromatography assay technique. Structured questionnaires were administered to households identified at pig rearing areas to obtain the population structures and some information on managemental practices. Results: A total number of 849 pigs were enumerated at 37 pigs rearing households. Tudun wada had the largest concentration of pigs (237 pigs), while Dabai has the least (38 pigs). A total of 250 blood samples were collected, of which 45 (18%) were positive; Zango has the highest seroprevalence (1.6%), while Dabai recorded the least (0.4%). Based on sex and age, the infection was higher in female (10.4%) and young pigs (11.6%) than male (7.6%) and adult pigs (6.4%), respectively. There was no significant (p>0.05) association between infection and pig rearing areas, sex, and age. Furthermore, none of the 250 pigs examined for classical FMDV lesions was positive. Conclusion: The results of this study showed that FMD is an important disease of pigs in the study areas. This result justifies the need for more attention and subsequent molecular study to identify the circulating FMDV in the area, which will help in the implementation of effective control measures.